Analisis Sifat Fisik dan Mekanik Sambungan Las Oxy-Acetylene pada Pelat Baja Karbon Rendah dengan Variabel Nyala Torch Karburasi - Andika Wisnujati; Ahmad Nurhuda (Proklamasi 45 University, 2017)
Oxy-acetylene welding is widely used in small workshops for car body repair, automobile and motorcycle exhaust, and other improvements using a maximum temperature of 3000oC that can not be done through another process. The purpose of this study was to analyze the effect of torque oxyacetylene flame carburizing on the physical-mechanical properties of low carbon steel plate welding joints. The method employed by using a low carbon steel plate 2 (two) pairs in a butt weld immension of 300 mm x 75 mm x 1 mm. After welding with oxy-acetylene in torch carburizing flame, the specimens were examined through physical observation including microstructure and echanical properties. Micro hardness vickers (VHN) was used to evaluate the harness and tensile properties was determine using the universal testing machine. In the microstructure testing, there is a pearlite and ferrite whose become different dimensions as it is affected by the heat and air pressure of the weld. The result of tensile strength specimen A 174,6 N/mm2 and specimen B 157,65 N/mm2. While the vickers test obtained the highest hardness that is 152.5 VHN in the welding area.